Matthew - Talbert, Charles H. (Grand Rapids, Mich. : Baker Academic, 2010)
A leading New Testament scholar examines cultural context and theological meaning in Matthew. This commentary approaches each text in its final, canonical form, proceeding by sense units rather than word-by-word or verse-by-verse. Each sense unit is explored in three sections: (1) introductory matters, (2) tracing the train of thought, (3) key hermeneutical and theological questions--From publisher description.
Matthew 1:1-2:23. Birth narratives -- Matthew 3:1-8:1. Part 1: Jesus's ministry begins -- Matthew 8:2-11:1. Part 2: Jesus's authority is revealed -- Matthew 11:2-13:53. Part 3: Jesus's ministry creates division -- Matthew 13:54-19:2. Part 4: Jesus focuses on his disciples -- Matthew 19:3-26:1a. Part 5: Jesus and judgment -- Matthew 26:1b-28:20. Passion and resurrection narrative.
Includes bibliographical references (pages 325-345) and indexes.
Keywords: Bible. -- Commentaries